Long-term outcome and risk factors of reintervention after high intensity focused ultrasound ablation for uterine fibroids: a systematic review and meta-analysis - Yuya Dou; Lian Zhang; Yu Liu; Min He; Yanzhou Wang; Zhibiao Wang (International Journal of Hyperthermia)
Objectives To quantify the reintervention rate and analyze the risk factors for reintervention after high-intensity focused ultrasound (HIFU) ablation of uterine fibroids.Methods Eighteen studies were selected from the seven databases. A meta-analysis was applied to synthesize the reintervention rates for fibroids across various follow-up durations. Subgroup-analysis was conducted based on the year of surgery, sample size, guide methods, and non-perfusion volume ratio (NPVR). Signal intensity of T2-weighted imaging (T2WI) was independently evaluated for reintervention risk.Results The study enrolled 5216 patients with fibroids treated with HIFU. There were 3247, 1239, 1762, and 2535 women reaching reintervention rates of 1% (95% confidence interval (CI): 1-1), 7% (95% CI: 4-11), 19% (95% CI: 11-27), and 29% (95% CI: 14-44) at 12, 24, 36, and 60-month after HIFU. The reintervention rates of patients treated with US-guided HIFU (USgHIFU) were significantly lower than those of patients treated with MR-guided focused ultrasound surgery (MRgFUS). When the NPVR of fibroids was over 50%, the reintervention rates at 12, 36 and 60-month after HIFU were 1% (95% CI: 0.3–2), 5% (95% CI: 3–8), and 15% (95% CI: 9–20). The reintervention risk for hyper-intensity fibroids on T2WI was 3.45 times higher (95% CI: 2.7–4.39) for hypo-/iso-intensity fibroids.Conclusion This meta-analysis showed that the overall reintervention rates after HIFU were acceptable and provided consultative suggestions regarding treatment alternatives for patients with fibroids. Subgroup-analysis revealed that USgHIFU, NPVR ≥ 50%, and hypo-/iso-intensity of fibroids on T2WI were significant factors in reducing reintervention.Systematic Review Registration PROSPERO, CRD42023456094